2006
DOI: 10.1248/bpb.29.2279
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Liposomal Naphthoquinone Esters Isolated from Thai Medicinal Plant: Rhinacanthus nasutus KURZ.

Abstract: Rhinacanthus nasutus KURZ. (family Acanthaceae), has been used in Thai traditional medicine for the treatment of various diseases such as eczema, pulmonary tuberculosis, herpes, hepatitis, diabetes, hypertension and various skin diseases, and its active components were widely investigated. 1-7)R. nasutus KURZ. has also been used for cancer treatment. [8][9][10] The main bioactive compounds were revealed to be naphthoquinone; rhinacanthins (A-D, G-Q), rhinacanthone and lignan groups. [1][2][3][4][5][6][7][8]10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 32 publications
0
40
0
2
Order By: Relevance
“…The same group have also shown that when these naphthoquinone esters are liposomalized with egg yolk phosphatidylcholine (EPC) and egg yolk phosphatidylglycerol (EPG), there was significant increase in the antiproliferative effects on HeLa cells as measured by cell proliferation assay (Siripong et al, 2006b). The proliferation of the cells was significantly inhibited by rhinacanthins when the concentration of these drugs was increased from 3-300 mM and the exposure time was prolonged to 24-72 h. The IC 50 values of rhinacanthins-C, -N and -Q were 32, 17 and 70 mM for 24 h; 19, 17 and 52 mM for 48 h; and 2.7, 2.0 and 5.0 mM for 72 h incubation, respectively.…”
Section: Naphthoquinone Estersmentioning
confidence: 95%
“…The same group have also shown that when these naphthoquinone esters are liposomalized with egg yolk phosphatidylcholine (EPC) and egg yolk phosphatidylglycerol (EPG), there was significant increase in the antiproliferative effects on HeLa cells as measured by cell proliferation assay (Siripong et al, 2006b). The proliferation of the cells was significantly inhibited by rhinacanthins when the concentration of these drugs was increased from 3-300 mM and the exposure time was prolonged to 24-72 h. The IC 50 values of rhinacanthins-C, -N and -Q were 32, 17 and 70 mM for 24 h; 19, 17 and 52 mM for 48 h; and 2.7, 2.0 and 5.0 mM for 72 h incubation, respectively.…”
Section: Naphthoquinone Estersmentioning
confidence: 95%
“…Major attention has been focused on identifying phytochemicals that can inhibit tumor development processes (Siripong et al, 2006(Siripong et al, , 2009. Glycosmis parva Craib (Rutaceae) is a wild small shrub found in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Siripong and coworkers reported that among rhinacanthins, rhinacanthin-N significantly suppressed tumor growth in vivo (Siripong et al, 2006). It has been reported that rhinacanthone isolated from R. nasutus roots induced apoptosis in human cervical carcinoma cells (Siripong et al, 2009).…”
Section: Disscussionmentioning
confidence: 99%